2019
DOI: 10.5114/wiitm.2019.88660
|View full text |Cite
|
Sign up to set email alerts
|

Posterior percutaneous endoscopic cervical foraminotomy and discectomy for degenerative cervical radiculopathy using intraoperative O-arm imaging.

Abstract: IntroductionPosterior percutaneous endoscopic cervical foraminotomy and discectomy (P-PECD) is a minimally invasive technique for the treatment of degenerative cervical radiculopathy. The O-arm, an intraoperative mobile computed tomography (CT) scanner, may improve spine surgery outcomes.AimTo evaluate clinical outcomes of O-arm assisted P-PECD in patients with degenerative cervical radiculopathy.Material and methodsBetween January 2013 and January 2018, 32 patients with degenerative cervical radiculopathy who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…In this study, PECF data reported in 9 published studies were analyzed (Table 1 ). [ 13 21 ] Two of these 9 studies were prospective, while the other 7 studies were retrospective. A total of 486 patients (male:female = 230:256) were included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, PECF data reported in 9 published studies were analyzed (Table 1 ). [ 13 21 ] Two of these 9 studies were prospective, while the other 7 studies were retrospective. A total of 486 patients (male:female = 230:256) were included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it can be di cult to nd and repeatedly con rm the V point of the surgical segment under C-arm uoroscopy during the operation. Researchers have proposed that O-arm uoroscopy could be used for 3D imaging to locate the V point during the operation, 21,22 and cervical spine lateral mass vertical anchoring has shown promise for use in surgical positioning. 14 The projection point on the inner upper edge of the pedicle is a bony structure, that does not change with dynamic changes in the position of the cervical spine during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Superior to the MED technique, a percutaneous spinal endoscopic procedure is widely applied in cervical and lumbar spine disorders to achieve excellent surgical visualization [ 15 ], an enlarged visual field due to the use of optical instruments, less iatrogenic trauma, and a faster postoperative recovery process. With growth of experience among spinal surgeons, improvement in surgical instruments, and the ability to achieve adequate bone and soft tissue resection, the scope of indications for the percutaneous spinal endoscopic technique has expanded [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of surgical techniques and instruments, good results and advantages have been described for full-endoscopic discectomy techniques for lumbar stenoses and cervical spondylosis myelopathy [13][14][15]. However, few reports have explored the use of posterior percutaneous full-endoscopic ligamentectomy decompression (p-PELD) for TM caused by OLF.…”
Section: Introductionmentioning
confidence: 99%